Experimental and theoretical studies on corrosion inhibition of mild steel in hydrochloric acid by thiosemicarbazone of Schiff bases. (April 2014) - Yadav, M.; Behera, D.; Kumar, S.
<x content-type="archive" xml:space="preserve">Abstract</x> The inhibiting action of the synthesised thiosemicarbazones, namely, 4[N-(4′-chlorobenzalidene)amino] antipyrinethiosemicarbazone, 4[N-(benzalidene)amino] antipyrinethiosemicarbazone, and 4[N-(4′-methoxybenzalidene)amino] antipyrinethiosemicarbazone towards the corrosion behaviour of mild steel in 4M HCl solution was studied by using weight loss, potentiodynamic polarisation and electrochemical impedance spectroscopy techniques. Scanning electron microscopy was used to characterise the surface morphology of the mild steel specimens in the presence and absence of inhibitor. The experimental results show that the inhibition efficiency increases as the concentration of the inhibitors were increased. The polarisation measurements indicate that the studied inhibitors act as mixed inhibitor. The adsorption of studied inhibitors on mild steel surface obeys Langmuir adsorption isotherm. Quantum chemical calculations were carried out by using semi-empirical AM1 method. A good correlation between the theoretical data and the experimental results was found. On a étudié l'action inhibitrice des thiosemicarbazones synthétisées, c'est-à-dire, 4[N-(4′-chlorobenzalidène)amino] antipyrinethiosemicarbazone, 4[N-(benzalidène)amino] antipyrinethiosemicarbazone, et 4[N-(4′-méthoxybenzalidène(amino] antipyrinethiosemicarbazone par rapport au comportement à la corrosion de l'acier doux dans une solution d'HCl 4M en utilisant les techniques de perte de poids, de polarisation potentiodynamique et de spectroscopie d'impédance électrochimique. On a utilisé la microscopie électronique à balayage pour caractériser la morphologie de la surface des échantillons d'acier doux avec ou sans inhibiteur. Les résultats expérimentaux montrent que l'efficacité de l'inhibition augmente avec l'augmentation de la concentration des inhibiteurs. Les mesures de polarisation indiquent que les inhibiteurs étudiés agissent comme un inhibiteur mixte. L'adsorption des inhibiteurs étudiés à la surface de l'acier doux obéit à l'isotherme d'adsorption de Langmuir. On a effectué des calculs chimiques quantiques en utilisant la méthode semi-empirique AM1. On a trouvé une bonne corrélation entre les données théoriques et les résultats expérimentaux.